Effects of Pilates on inter-recti distance, thickness of rectus abdominis, waist circumference and abdominal muscle endurance in primiparous women - Namee Lee; Young-Hyeon Bae; Shirley S. M. Fong; Wan-Hee Lee (BMC, 2023)
Abstract Background Pilates is expected to have a positive effect on women with weakened abdominal muscles after childbirth. Pilates may have a beneficial effect on the structure and function of the abdominal muscles in pregnant women. Therefore, the objective of this study was to investigate the effects of Pilates on inter-recti distance, thickness of the rectus abdominis, waist circumference, and abdominal muscle endurance in primiparous women. Methods Thirty-five primiparous postpartum women were assigned to either the Pilates exercise group (n = 20) or the control group (n = 15). Pilates was undertaken by the exercise group for 50 min/day, 5 days/week, for 4 weeks. The control group maintained their daily activities without any intervention. The inter-recti distance was measured at three locations along the linea alba, and the thickness of the rectus abdominis was measured using ultrasound. Abdominal muscle endurance was measured using a repeated 1-min curl-up test. Waist circumference was also measured. Results The exercise group showed significant improvements from baseline in inter-recti distance, waist circumference, and abdominal muscle endurance (p < 0.05). The control group showed no significant improvement in these variables. Compared with the control group, the exercise group showed significantly improved performance in terms of inter-recti distance, waist circumference, and abdominal muscle endurance (p < 0.05). Conclusions The results of this study demonstrate that Pilates was effective in reducing inter-recti distance and waist circumference and improving abdominal muscle endurance in primiparous postpartum women. Pilates is considered an effective exercise for improving muscle structure and function in primiparous postpartum women, helping in the recovery from, and preventing, diastasis rectus abdominis.